NEONATAL SEIZURES ETIOLOGICAL AND CLINICAL DIFFERENTIATION - SHASHIDHAR VEERAPPA; PRASHANTH BASUTKAR; SHILPA N; VINODCHANDRAN; SREEKANTHA (International Journal of Pharma and Bio Sciences, 2013)
The fits occurring from birth to the end of neonatal period is commonly referred as Neonatal seizures; this period is one of the most important period in life time, which is susceptible for the development of seizures. The small injury in the form of mechanical malhandling to the highest genetic or congenital disorders will manifest in the form of seizures, which may become the etiology for long standing seizures. This study focuses mainly the etiological factors which may contribute for the development of neonatal seizures and clinical differentiation of the same.